Proceedings of the ACM 2012 Conference on Computer Supported Cooperative Work Companion 2012
DOI: 10.1145/2141512.2141585
|View full text |Cite
|
Sign up to set email alerts
|

Exploring automation in digital tabletop board game

Abstract: Digital tabletops present the opportunity to combine the social advantages of traditional tabletop games with the automation and streamlined gameplay of video games. However, it is unclear whether the addition of automation enhances or detracts from the game experience. A study was performed where groups played three versions of the cooperative board game Pandemic, with varying degrees of automation. The study revealed that while game automation can provide advantages to players, it can also negatively impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 2 publications
1
20
1
Order By: Relevance
“…Overall, groups had a high level of situation awareness, in contrast to results from a previous study of a digital version of Pandemic [42] and from our training condition, both of which offered no mechanism for players to explore past events. This finding suggests that the timelines were effective in providing relevant historical game information.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Overall, groups had a high level of situation awareness, in contrast to results from a previous study of a digital version of Pandemic [42] and from our training condition, both of which offered no mechanism for players to explore past events. This finding suggests that the timelines were effective in providing relevant historical game information.…”
Section: Discussioncontrasting
confidence: 98%
“…study to rapidly prototype design concepts, and to enable lab-based studies with a complex task for which "experts" could be easily recruited. Moreover, Pandemic has been shown to elicit the out-of-the-loop automation problem [42].…”
Section: Figure 1: Interactive Event Timelines A) Cut-out Of the Inimentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, realistic task behavior is likely to occur during the study, improving the validity of study results. Finally, previous research has shown similar, negative impacts of automation on situation awareness in digital tabletop board games consistent with automation research in other application areas [8].…”
Section: Introductionsupporting
confidence: 85%
“…This can leave users unable to respond appropriately to critical system events. The problem of situation awareness has been observed in both traditional [2] and tabletop interfaces [8]. Tabletops both require and afford powerful solutions to this problem through their collaborative directlymanipulated nature.…”
Section: Introductionmentioning
confidence: 99%